Anti-SARS-CoV-2 Seroconversion in COVID-19 Convalescent Kidney Transplant Recipients Compared with Non-transplanted Patients - Garcia, Ricardo Martins (2023)
Objective: Due to immunosuppression, kidney transplant recipients (KTRs) might have lower seroconversion after COVID-19 than non-KTRs. Thus, we aimed to evaluate the seroconversion rate after COVID-19 between KTRs and non- KTRs. Methods: This cohort study enrolled three non-paired groups of patients with COVID-19: 601 KTRs, 211 healthcare workers (HCWs), and 170 non-transplanted inhabitants (INHs) in a countryside city in Brazil. The anti-severe acute respiratory syndrome coronavirus 2 nucleocapsid antibody was assessed 14 days after diagnosis. The primary outcome was seroconversion. Results: The KTRs were older, had more comorbidities and severe COVID-19. Compared to HCWs and INHs, admission to the intensive care unit (ICU; 44.9% vs. 0% vs. 1.8%, p<0.001), mechanical ventilation requirement (32.3% vs. 0% vs. 1.8%, p<0.001), and death (28.8% vs. 0% vs. 1.2%, p<0.001) were significantly higher in KTRs. Seroconversion did not differ between the groups: 76.2% in KTRs, 74.9% in HCWs, and 82.2% in INHs (p=0.35). In a group-adjusted multivariable logistic regression, while a short period between infection and blood sample collection reduced the probability of seroconversion (adjusted odds ratio [aOR]=0.986), the presence of fever (aOR=1.737, p=0.017), cough (aOR=1.785, p=0.005), and requirement for ventilatory support (OR=1.981, p=0.017) increased the risk. Conclusions: Clinical severity, mechanical ventilation requirement and death by COVID-19 were significantly higher among the KTRs. However, amongthe survivors, KTRs had a similar seroconversion prevalence associated with clinical severity parameters and a shorter time of blood sample collection.